Actinic Keratosis Clinical Practice Guidelines: An Appraisal of Quality. (16th September 2015) - Kirby, Joslyn S.; Scharnitz, Thomas; Seiverling, Elizabeth V.; Ahrns, Hadjh; Ferguson, Sara
Abstract : Actinic keratosis (AK) is a common precancerous skin lesion and many AK management guidelines exist, but there has been limited investigation into the quality of these documents. The objective of this study was to assess the strengths and weaknesses of guidelines that address AK management. A systematic search for guidelines with recommendations for AK was performed. The Appraisal of Guidelines for Research and Evaluation (AGREE II) was used to appraise the quality of guidelines. Multiple raters independently reviewed each of the guidelines and applied the AGREE II tool and scores were calculated. Overall, 2, 307 citations were identified and 7 fulfilled the study criteria. The Cancer Council of Australia/Australian Cancer Network guideline had the highest mean scores and was the only guideline to include a systematic review, include an evidence rating for recommendations, and report conflicts of interest and funding sources. High-quality, effective guidelines are evidence-based with recommendations that are concise and organized, so practical application is facilitated. Features such as concise tables, pictorial diagrams, and explicit links to evidence are helpful. However, the rigor and validity of some guidelines were weak. So, it is important for providers to be aware of the features that contribute to a high-quality, practical document.